Analysis of the Scientific Production of Nursing in Older People with Cancer in Palliative Care: Bibliometric Study - Dayara de Nazaré Rosa de Carvalho; Fabiana de Souza Orlandi; Viviane Ferraz Ferreira de Aguiar; Sofia Cristina Iost Pavarini; Dandara de Fátima Ribeiro Bendelaque; Monique Lindsy de Souza Baia; Luana Cunha Galvão Pereira; Marcela Raíssa Asevedo Dergan; Ivonete Vieira Pereira Peixoto (Archives of Current Research International, 2023)
Aims: to analyze and map the international production on Nursing Care for the elderly with cancer in palliative care, between 2000 and July 2021. Methods: this is a descriptive, exploratory and mixed-approach study that can be classified both a bibliometric and scientometric research. Data collection took place from June to July 2021, in the Scopus (Elsevier) database. After defining the inclusion and exclusion criteria, the collection began, which resulted in the final sample consisting of 198 publications. After the entire selection process, the dataset was saved in a single file in CSV Excel format, where it was later exported to the VOSviewer® software. Results: it was shown that most selected publications are concentrated between the years 2019 with 44 (22.22%) publications, 2018 with 37 (18.69%) publications. The United States appears as the country with the largest majority of co-authors, with 81 (40.91%) documents and 750 citations, and the first 15 authors who most published on the subject are from the United States, followed by authors from Canada and Sweden. Conclusion: this review showed that publications covering the subject are still limited when related to nursing. However, despite the few existing publications, there is a growing increase in the quantity of publications over the years, which indicates the relevance that the topic has gained in the academic world.